Arylseleninic acid derivative decomposition towards Se(ii)-based electrophiles: an elegant approach to construct 3-selanyl-imidazopyridines. (10th March 2023) - Anghinoni, João M.; Ferreira, Sabrina S.; Schumacher, Ricardo F.; Iglesias, Bernardo A.; Perin, Gelson; Penteado, Filipe; Lenardão, Eder J.
Abstract : A total of thirty-four 3-selanylimidazopyridines were easily prepared in 50–94% yields using bench stable arylseleninic acids as a selenium source. Abstract : Benzeneseleninic acid (BSA) derivatives were used as an alternative, but extremely useful, source of Se(ii )-based electrophiles, generated in situ by thermal decomposition, to construct C–Se bonds, accessing 3-selanylimidazopyridines after reaction with 2-substituted imidazopyridines. A total of thirty-four derivatives were synthesized in 50–94% yield, seventeen of which were so far unprecedented. A simple and efficient protocol is described, just delivering H2 O and diaryl diselenide as by-products. Diaryl diselenides can be easily recovered during the purification process and converted again to BSA for a new reaction.